Pengembangan Museum Ranggawarsita Sebagai Salah Satu Destinasi Wisata 2013-2018 ( Sebuah Kajian Sejarah Publik) - RAKHIM, REZA ANDIKA (Journal of Indonesian History, 2021)
The development of the Ranggawarsita Museum as a tourist destination in 2013-2018 is an effort made by museum managers to increase public interest in visiting museums and maintaining and preserving cultural historical heritage in Central Java. The existence of a public history study from several experts aims so that the views and input from museum experts and cultural experts can be used as material to improve the quality of the Ranggawarsita Museum. The main problem that will be discussed in this paper is how the study of public history relates to the Ranggawarsita Museum and how to package the development of the Ranggawarsita Museum. This research was conducted with a purpose, including explaining how the Ranggawarsita Museum in the perspective and study of public history, the efforts of the Ranggawarsita Museum management in integrating Semarang tourist destinations with the Ranggawarsita Museum especially after the SKPD Plan and Strategy regulations issued by the Dinas Kebudayaan dan Pariwisata in 2013 , as well as how to package and update museum displays. This research was conducted using historical research methods. The results of this study found the Ranggawarsita Museum as a public history medium and as a place for historical heritage from the cultural results of the people of Central Java that can build, explore and maintain the community's collective memory of history in the past and must become one of the tourist destinations in order to maintain its existence and increase visits. to the Ranggawarsita Museum after the SKPD Plan and Strategy regulation issued by the Culture and Tourism Office. This study reveals several obstacles faced by the Ranggawarsita Museum as a tourist destination.